Enhancing Numeracy Skills of Remedial Class Learners Through Multisensory Learning Strategies: An Action Research - Dela Cruz, Julie Ann C.; Condino, Ralph Michael B.; Sombilon, James Paul M.; Tabasa, Jushua; Sagge, Jr., Roberto G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This action research aimed to enhance the numeracy skills of Grade 9 remedial learners at a high school in Iloilo Province through multisensory learning strategies. Recognizing the persistent struggles in mathematics among the remedial learners, the researchers implemented a three-week intervention using three distinct approaches: tactile learning through manipulatives, audiovisual learning through educational videos, and kinesthetic learning through movement-based games. Sixteen identified remedial learners participated in activities that engaged multiple senses to make abstract concepts more concrete and accessible. Assessment results showed a clear before-and-after improvement in numeracy performance, from a Week 1 baseline mean score of 14.44/40 (36.10%) to a Week 3 post-intervention mean score of 32.88/40 (82.20%), with kinesthetic activities yielding the highest impact—100% of learners scoring 50% and above by the end of the intervention (compared with 18.75% in Week 1 and 56.25% in Week 2). Student interviews confirmed that games, visual presentations, and active participation improved engagement, comprehension, and enjoyment. Simple incentives like snacks and sticker-based attendance cards further boosted motivation and consistent attendance. The data analysis highlighted that engaging multiple senses supports differentiated instruction, improves learning outcomes, and fosters a more inclusive and interactive environment for struggling learners. The study recommends regular integration of multisensory learning strategies, particularly kinesthetic learning strategy through movement-based games, in remedial instruction, along with incentives that sustain student interest. This research provides practical and evidence-based insights for educators seeking to transform traditional math instruction and support diverse learning needs in remedial settings.